Development of laser-based joining technology for the fabrication of ceramic thermoelectric modules. Issue 16 (12th September 2014) - Börner, Floriana-Dana; Schreier, Max; Feng, Bing; Lippmann, Wolfgang; Martin, Hans-Peter; Michaelis, Alexander; Hurtado, Antonio
Abstract